Experimental study of the VFD's speed stabilization processes under torque disturbances - Vladimir L. Kodkin; Aleksandr S. Anikin (Institute of Advanced Engineering and Science, 2023)
Maintaining speed with various jumps and changes in load torque is one of the main tasks of variable frequency drives (VFD). The article considers the operation of the VFD under the influence of periodic perturbations of variable frequency and amplitude. The dependence of the transient function of the VFD and the family of frequency characteristics associated with it on the frequency of the stator voltage and slip underlies the methodology for experimental studies of such drives. The traditional method is based on the response to harmonic stimulation and works well for a non-linear system. In the course of the work, it was found that the introduction of dynamic positive feedback (DPF) allows to compensate for disturbances of varying frequency and amplitude. Experiments with a sinusoidal change in the load torque have shown the effectiveness of introducing the DPF in front of conventional sensorless control systems (vector and scalar).